INVASI YUNANI KE PERSIA SEBAGAI BUKTI KEBANGKITAN KEBUDAYAAN HELLENIS - Anisa Septianingrum (Universitas Negeri Padang, 2018)
Persia and Greece have engaged in a complicated relationship with war in the expansion of the territory. Persia was superior first because it was able to form strong empires and conquer cities around Asia and several cities in Europe. Greece managed to get rid of Persia, but it did not last long. Greece in ancient times consisted of many policies that competed with each other. The most famous policies of that period were Athens and Sparta. Both have advantages compared to other policies scattered in Greece. However, Athens and Sparta are two policies that compete with their respective strengths, causing disputes. Persia at that time had established good relations with Athens and Sparta. Persia found great opportunities to control Greece in the event of a war between Athens and Sparta. Persian interference in Greece was unavoidable which led to the Peloponnesian War which resulted in the conquest of Persia over Greece. Greece's downfall under the conquest of Persia did not last long. A unifying figure emerged in Greece that was able to embrace all policies and become the greatest king in history who had a vast conquest, both in the West and East. Alexander The Great was a king from the Kingdom of Macedonia in Greece who was able to unite all policies. Alexander invaded Persia to spread Hellenic culture.